Calculation of coupling coefficient caused by vertical dispersion - Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2001)
Sources of horizontal-vertical coupling of transverse oscillations in storage rings are misalignments and tilts of bending magnets, quadrupoles and sextupoles. The coupling arises from two separate factors: spurious vertical dispersion generated by misalignment errors and skew-quadrupole effects generated by tilts of magnet elements. It is sensible to consider the effect of these factors to vertical emittance apparently with the aim to determine an influence of the each factor and to define methods of the coupling correction. In this paper a method of a coupling coefficient determination caused by spurious vertical dispersion in an electron storage ring is presented. The method is base on a matrix formalism of a coupling motion description and allows take distribution function of the coupling coefficient. The results of the coupling coefficient calculations for the Kharkov source of synchrotron radiation (UNK) are presented.